Strengthening Sharia Financial Literacy and Portable Marketing for the Tengger Tribe Community - Bakhri, Saiful; I Nyoman Budiono; Sulistyowati; Siti Hasanah; Ahmad Fauzan Mubarok; Khotibul Umam; Nadia Azalia Putri; Ana Pratiwi; Hasnah Haron; Nur Aima Shafie; Siti Kadariah (Yayasan Darussalam Patalassang, 2025)
This community service program aims to enhance the economic independence of the Tengger Tribe through strengthening Islamic financial literacy and portable digital marketing skills. The program was conducted as an international collaboration between Indonesian universities that are members of APSKPS and Malaysian universities, namely Universiti Sains Islam Malaysia (USIM), Universiti Teknologi MARA (UiTM), and Universiti Kebangsaan Malaysia (UKM). The study employed a Participatory Action Research (PAR) approach, involving the community actively in each stage of the program, from planning to implementation and evaluation. The results indicate an increased understanding among participants regarding Islamic financial principles, including contracts such as mudharabah, musyarakah, and murabahah, as well as the application of simple financial record-keeping in small enterprises. Moreover, the portable marketing training encouraged local entrepreneurs to utilize digital platforms such as WhatsApp Business and Instagram to promote Tengger’s local products to a broader market. This program successfully fostered cross-country academic collaboration and demonstrated that the synergy between education, Islamic values, and digital technology can serve as an effective strategy in developing an equitable and competitive indigenous economy.